Conservation and structural stabilization of al Hayla tower in the Liwa Oasis, Abu Dhabi. Issue 1 (4th May 2019) - Marcus, B.; Ziegert, C.; Paganoni, S.; Mahdy, H.; Muhammad, S.
ABSTRACT: Al Hayla tower is a historic stone building located in Liwa Oasis in the vast 'Empty Quarter' desert of Abu Dhabi, United Arab Emirates. As one of the few remaining unaltered stone buildings in the emirate, Halya is a rare record of stone construction techniques and a significant part of Abu Dhabi's heritage. When first surveyed in 2009, the tower was in critical condition with large vertical cracks that threatened to cause total collapse of the structure. Emergency conservation measures including shoring and strapping were carried out and a conservation management plan was drafted to guide future interventions. Documentation, materials analysis and treatment trials were also carried out followed by conservation. The interventions included structural reinforcement, grouting, repointing, and application of a shelter coat. Geogrid fiber was chosen for reinforcement because of its high tensile strength and resistance to heat deformation and corrosion in the desert environment. After several years of monitoring following the interventions, the tower has remained stable. This paper describes the conservation and structural stabilization work in detail, focusing on materials analysis, mortar selection, and the conservation and structural solutions chosen to stabilize the tower.